The Effect of Remuneration, Work Motivation and Job Satisfaction on Employees Performance - Rapsanjani, Anggi; Johannes, Singmin (International Humanities and Applied Science Journal, 2019)
This study aims to analyze the effects of remuneration, work motivation, and job satisfaction on employees performance. The object of this study are employees working at Housekeeping Department of PT XYZ. This research was conducted to 153 respondents (proportionate simple random sampling) from the total populations of 246 employees. Determination of the number of samples to this research by using the Slovin Formula on employees at the Housekeeping Department of PT. XYZ. This research used quantitative approach by distributed questionnaires. The analyzing used Multiple Linear Regression (SPSS version 23). The results of this study indicate that remuneration, work motivation and job satisfaction have significant positive effects on employees performance. Job satisfaction variable is the most influential variable followed by work motivation and remuneration. It is suggested that the management of PT XYZ to pay attention to promotion policy by multiplying the information about promotion. Its implementation should be more open and involving union so that all employees have the equal opportunities to get their career advancement.